Playful pets - Matthes, Dianne; Watson, Brain (Brown Watson England, 1986)
Animal Chatterbook series by Brian Watson. It introduces young readers to a delightful cast of animal characters, each with their own unique traits and stories. Through engaging illustrations and simple text, the book encourages curiosity about the animal kingdom and fosters a love for reading.